INFLUENCE OF STORAGE SYSTEMS ON GRAPES VALUE CHAINS IN DODOMA RURAL FARMERS - Sama, Hamisi K (Socio-Economics/Agribusiness Department, 2024)
Grapes cultivation in Dodoma Rural stands as a cornerstone of agricultural activity, emblematic of the region's agrarian heritage and economic potential. The multifaceted dynamics of the grape value chains in Dodoma Rural epitomize a complex interplay of agricultural, economic, and social dimensions. The research aims to provide actionable insights on influence of storage systems on grapes value chains in Dodoma rural farmers. A total of 133 respondents took part in the study through stratified random sampling, where data were analysed by descriptive, correlation analysis and regression analysis. The results suggests that increases in storage systems are associated with increase in the Grapes Value Chains and that improvement can increases motivation for increase of the grape production and cultivation to Dodoma rural farmers.